Analisis Cash Conversion Cycle, Capital Expenditure dan Investment Opportunity Set dalam Mengoptimalkan Cash Holding - Farach Dhiba Helmaliana; Nor Norisanti; Erry Sunarya (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
ABSTRACT. The research was aimed at determining how much influence the Cash Conversion Cycle, Capital Expenditure and Investment Opportunity Set have in optimizing Cash Holding in food and beverage subsector companies listed on the Indonesia Stock Exchange for the period 2018-2022. The objects in this study are Cash Conversion Cycle (X1), Capital Expenditure (X2) Investment Opportunity Set (X3) and Cash Holding (Y). This research uses descriptive methods with a quantitative approach. The sampling technique used in this study used a non-probability sampling approach with purposive sampling method. The data analysis technique used is multiple correlation coefficient test, determination coefficient test, multiple linear regression test, partial test (t test) and simultaneous test (F test). Based on the results of the study, it shows that there is a variable relationship between Cash Conversion Cycle, Capital Expenditure and Investment Opportunity Set in optimizing Cash Holding of 0.749 which means that the level of relationship between Cash Conversion Cycle, Capital Expenditure and Investment Opportunity Set in optimizing Cash Holding is included in the strong relationship criteria. Then the partial test results show that the Cash Conversion Cycle has a positive and significant effect in optimizing Cash Holding, Capital Expenditure has no effect in optimizing Cash Holding, and Investment Opportunity Set has a positive and significant effect in optimizing Cash Holding